Pengaruh Lumpur Laut Cair Serta Pemeberian Pupuk Kandang Sapi dalam Budi Daya Tanaman Cabai Rawit (Capsicum frutescens, L) Pada Lahan Gambut - Hrp, Rahmi Sari; Srg, Rianto Joni (JURNAL AGROPLASMA, 2023)
This study to determine the effect of liquid sea mud and cow dung on the growth and yield of cayenne pepper plants on peat soils was carried out on the land of residents of Tnjung Rejo Paloh Panglima village, Percut Sei Tuan District, Deli Medium Regency, North Sumatra Province, from May to August 2023. The study was arranged in a Complete Randomized Design with two factors and each treatment combination was replicated three times. The first factor is the dose of liquid coastal sediment (0; 0.5; 1; 1.5 L/ plant), while the second factor is the dose of cow dung (0; 50; 100; 150 g/ plant). The results of the first experiment showed that there was no interaction between liquid sea mud and cow dung in affecting plant height, dry weight of plants, number of fruit plants, weight of chili plants and plant weight, While the application of cow dung significantly increases plant height, dry weight of plants and weight of fruit crops. Application of liquid sea mud plants 1 L and cow dung 100 g / plant can promote soybean growth and yield in peat soils. Keywords : Cayenne pepper, Sea mud, cow dung